FEATURES OF THE DEVELOPMENT OF THE FOREIGN ECONOMIC ACTIVITY AT THE MODERN ENTERPRISE - М. О. Панченко; А. А. Капелюшна (Ринкова економіка: сучасна теорія і практика управління, 2018)
The article provides analysis of the main tasks of foreign economic activity of modern enterprises, and the main problems of its management. It is established that the updating of the enterprise’s foreign economic activity leads to the implementation and formation of a strategy of competitive advantages at the enterprise. The enterprises’ main features on the external market of commodity circulation are singled out and the algorithm of acceptance by the enterprise of administrative decisions on an exit on the external market is constructed.